2021
DOI: 10.1039/d1an01525g
|View full text |Cite
|
Sign up to set email alerts
|

Cross flow coupled with inertial focusing for separation of human sperm cells from semen and simulated TESE samples

Abstract: A triplet spiral channel coupled with cross-flow filtration has been designed and fabricated in an effort to separate sperm cells from either semen or simulated testicular sperm extraction (TESE) samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…[87][88][89] As these forces are particle size dependent, different cells are focused on distinct equilibrium positions to achieve continuous and high throughput (∼mL min −1 ) cell separation for different bio-fluids including blood, urine, 90 and semen samples. 91 When designing inertial cell sorters, it is important to consider both target and non-target cell sizes, starting sample concentration and volume, fluid properties, and channel dimensions for optimum focusing. 92 Abdulla et al reported a zigzag microchannel for label-free separation of CTCs from whole blood.…”
Section: Inertial Microfluidicsmentioning
confidence: 99%
“…[87][88][89] As these forces are particle size dependent, different cells are focused on distinct equilibrium positions to achieve continuous and high throughput (∼mL min −1 ) cell separation for different bio-fluids including blood, urine, 90 and semen samples. 91 When designing inertial cell sorters, it is important to consider both target and non-target cell sizes, starting sample concentration and volume, fluid properties, and channel dimensions for optimum focusing. 92 Abdulla et al reported a zigzag microchannel for label-free separation of CTCs from whole blood.…”
Section: Inertial Microfluidicsmentioning
confidence: 99%
“…[83][84][85][86] Another strategy involves the coupling of inertial microfluidics with another passive or active manipulation technique; for example, spiral inertial microfluidics has been integrated with a membrane filter, 87 deterministic lateral displacement (DLD), 88,89 and cross-flow filtration. [90][91][92] In the case of the two-stage inertial-DLD (i-DLD) sorter, a high sample purity of 93.59% was achieved for the separation of MCF-7 cells from blood cells. 88 Although DLD has a high separation accuracy, the integrated device cannot eliminate the essence of size-dependent separation and is still unable to separate cells with similar or overlapping sizes.…”
Section: Multistage Multiplexing and Multifunction Integration For Im...mentioning
confidence: 99%